Why do detention rates rise or fall?: a statistical and document analysis of the diverging Dutch and Belgian detention population trends between 2000 and 2020 - Boer, H. de (European journal of criminology, 2025)
Since 2005, detention rates in the Netherlands have decreased significantly, reversing prior growth. In contrast, neighbouring Belgium has experienced a substantial increase in its detention rates since the 1990s. By 2020 Belgium detained almost twice as many persons per 100,000 inhabitants as the Netherlands. The contrast between the two countries is striking as they are neighbouring countries with a partially shared history, language and criminal justice systems rooted in the French Penal Code. To understand these divergent detention trends, this study analyses systemic mechanisms that influence detention rates, focussing on criminal justice policies and penal decision-making. It does so by examining statistical data, literature and legislative and policy documents, distinguishing four detained groups, namely convicted persons in prison, persons in pre-trial detention, mentally ill incarcerated persons who are not criminally responsible, and persons in electronic detention, serving a detention period at home under electronic monitoring. The evolution of the convicted persons in prison and persons in electronic detention played a decisive role in the divergent trends in detention rates in the Netherlands and Belgium. In Belgium, the number of persons serving long(er) detention periods was much higher than in the Netherlands, and the actual time served by those convicted to prison sentences exceeding three years also increased, partly due to lengthy and complex conditional release procedures. This cross-national criminal justice research discusses limitations and presents directions for future research.